2015
DOI: 10.1002/mrm.25897
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous multislice (SMS) imaging techniques

Abstract: Simultaneous multislice imaging (SMS) using parallel image reconstruction has rapidly advanced to become a major imaging technique. The primary benefit is an acceleration in data acquisition that is equal to the number of simultaneously excited slices. Unlike in‐plane parallel imaging this can have only a marginal intrinsic signal‐to‐noise ratio penalty, and the full acceleration is attainable at fixed echo time, as is required for many echo planar imaging applications. Furthermore, for some implementations SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
489
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 456 publications
(504 citation statements)
references
References 104 publications
(194 reference statements)
5
489
0
10
Order By: Relevance
“…These multi-echo functional imaging techniques (Kundu et al, 2012) have shown great promise for improving the quality of fMRI data acquired from the brain, but have yet to be exploited for imaging the spinal cord. One might also use simultaneous multi-slice (or "multi-band") EPI, which allows a shortening of the TR due to the simultaneous excitation of several slices (Barth et al, 2016; interestingly, this approach has recently been combined with a multi-echo technique: Boyacioğlu et al, 2015); this approach requires a certain coil geometry, but would potentially allow one to critically sample cardiac and respiratory artefacts and thus remove them based on frequency spectra (which is not possible with standard TRs due to the aliasing that occurs). An alternative approach to improving the specificity of spinal cord fMRI is to reduce voxel sizes, which has been shown to reduce the influence of physiological noise (Hutton et al, 2011).…”
Section: Acquisitionmentioning
confidence: 99%
“…These multi-echo functional imaging techniques (Kundu et al, 2012) have shown great promise for improving the quality of fMRI data acquired from the brain, but have yet to be exploited for imaging the spinal cord. One might also use simultaneous multi-slice (or "multi-band") EPI, which allows a shortening of the TR due to the simultaneous excitation of several slices (Barth et al, 2016; interestingly, this approach has recently been combined with a multi-echo technique: Boyacioğlu et al, 2015); this approach requires a certain coil geometry, but would potentially allow one to critically sample cardiac and respiratory artefacts and thus remove them based on frequency spectra (which is not possible with standard TRs due to the aliasing that occurs). An alternative approach to improving the specificity of spinal cord fMRI is to reduce voxel sizes, which has been shown to reduce the influence of physiological noise (Hutton et al, 2011).…”
Section: Acquisitionmentioning
confidence: 99%
“…The application of SMS is also rapidly extending to the clinical domain for anatomical T 2 ‐ and normalT2*‐weighted imaging and below the neck. [For a review of technique and applications, see Barth et al 40 and Setsompop et al 41]. SMS is particularly attractive for high‐resolution 2D multislice imaging, which is time‐consuming due to the high number of phase‐encoding lines and slices that need to be acquired.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the distribution and amount of tissue heating with or without any conductive components placed in or near the RF coil is greatly affected by the coil size and design. For example, SAR values can be decreased by careful transmit coil design [62][63][64][65][66][67][68]. Kangarlu and co-workers performed simulations and experiments to study the impact of coil length on localized heating at 8T, showing greater heating for longer coils [69].…”
Section: Type Of Rf Transmit Coilmentioning
confidence: 99%